Reducing the Burden of Cervical Cancer in the Developing World - Agrawal, Priya (Current Women's Health Reviews, 2011)
Cervical cancer is the most common gynaecological cancer in developing countries. It is the single largest cause of life years lost to cancer in these settings, despite the existence of technology that could almost entirely prevent these deaths. Low-income countries face multiple challenges that prevent them achieving a reduction in burden of disease similar to that of the industrialised countries. Cytology-based programs are difficult to provide in resourcelimited settings, further compounded by socio-cultural factors such as lack of awareness amongst public, providers and politicians; cultural practices of child marriage and polygamy; as well as low levels of female literacy. However, despite these hurdles, there has been no better time to act than now. Widespread distribution of the HPV (Human Papillomavirus) vaccine and the adoption of new tools that enable a screen-and-treat approach have the potential to dramatically reduce the burden of cervical cancer. Increased recognition of the growing cancer burden, international resource-mobilisation and global collaboration will be necessary to stop women in developing countries dying of a wholly preventable disease.
Keywords: developing countries